Fast pyrolysis of rice husk under vacuum conditions to produce levoglucosan - Téllez Bernal, Jhoan Francisco (2021)
Levoglucosan (LG)-enriched pyrolytic oils were obtained from rice husk by lab-scale fast pyrolysis under vacuum conditions. We studied the effect of the pyrolysis temperature (300−700 °C) and the pretreatment of the biomass, on the pyrolysis product yields and the selectivity for LG formation. The maximum oil yield (47 wt.%) was obtained from hydrochloric acid-leached rice husk at 400 °C, producing 1.4 times more than the amount of oil produced from untreated rice husk at the same temperature. Anhydrosugars were the predominant compounds found in bio-oils under all conditions assessed, LG being the main product. Depending on the pyrolysis conditions, LG concentration was between 9−30 wt.% considering the bio-oil mass, and between 4−60 wt.% considering the initial cellulose mass. 1H NMR experiments were carried out as an alternative and simple technique to directly determine the amount of LG in bio-oils.